Cases in pediatric radiology : 200 cases (common diseases) : (conventional radiology, ultrasound, angiography, CT, MRI, nuclear medicine) - Haouimi, Ammar (Jaypee Brothers ; McGraw-Hill Medical, 2009)
Presents 200 common cases, with radiological descriptions of each disease, that are classified by body system: head and neck, chest and respiratory system, gastrointestinal system, genitourinary system, musculoskeletal system, and miscellaneous topics. This book covers imaging modalities, including conventional radiology, ultrasound, and MRI.